The study of the function of language and gender in the international court of Khatun Shirazi Based on DSL theory - Abbas-Ali Vafaie; Farideh Khajehpour (Matn/Pizhūhī-i Adabī, 2018)
One of the modern theories of linguistics and gender and language is DSL theory put forward by the eminent American linguist Robin Lakoff. According to this theory, the speech style of men and women is distinctive and different even in the most hidden cases. This is recognizable on the basis of dividing the gender structure of language into mind and lingual branches. The authors of this essay have used this theory to consider the language approach in Jahan Malek Khatoun’s poem that is the first female poet whose works are fairly complete. The main motive behind this study is some studies that have been conducted on the poetic style of Jahan Malek.  These studies have considered her style like the male poems style in terms of structure and language. Also, the female aspect of her poems has been neglected. The findings of the linguistic forms demonstrated that the high frequent use of words means companionship and cooperation. Mentally, words express female emotions explicitly which are the important signs for female language approach in Jahan Malek poems. In fact, Lakoff theory is a suitable model for considering literary works from gender and language perspective.